2019
DOI: 10.1021/acssuschemeng.9b00038
|View full text |Cite
|
Sign up to set email alerts
|

Europium-Doped Lead-Free Cs3Bi2Br9 Perovskite Quantum Dots and Ultrasensitive Cu2+ Detection

Abstract: Pollution triggered by highly toxic heavy metal ions has become of worldwide critical concern; thus, it is urgent to develop an eco-friendly and nontoxic fluorescence probe for metal ions sensing. The lead-free all-inorganic perovskite quantum dots (PeQDs) could be ideal candidates but are limited by their low photoluminescence quantum yield (PLQY). In this work, we successfully fabricated Eu3+-doped lead-free Cs3Bi2Br9 PeQDs employing a modified ligand-assisted reprecipitation method. The Cs3Bi2Br9:Eu3+ PeQD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 56 publications
3
72
0
Order By: Relevance
“…It was also shown that such Cs 3 BiBr 6 single crystals with band gap of 2.55 eV possess high thermal stability. To further improve PLQY of Cs 3 Bi 2 Br 9 perovskite NCs, a Eu 3+ -doping can be used via modified ligand-assisted reprecipitation (LARP) method as was shown in work [53]. The Cs 3 Bi 2 Br 9 :Eu 3+ NCs demonstrate multicolor emissions: Emission from the NC’ host Cs 3 Bi 2 Br 9 matrix and the Eu 3+ ion emissive transition.…”
Section: Synthesismentioning
confidence: 99%
“…It was also shown that such Cs 3 BiBr 6 single crystals with band gap of 2.55 eV possess high thermal stability. To further improve PLQY of Cs 3 Bi 2 Br 9 perovskite NCs, a Eu 3+ -doping can be used via modified ligand-assisted reprecipitation (LARP) method as was shown in work [53]. The Cs 3 Bi 2 Br 9 :Eu 3+ NCs demonstrate multicolor emissions: Emission from the NC’ host Cs 3 Bi 2 Br 9 matrix and the Eu 3+ ion emissive transition.…”
Section: Synthesismentioning
confidence: 99%
“…Fortunately, previous efforts have discovered many efficient lead-free emitters, e.g., double-perovskite [30][31][32] , copper [33][34][35] and bismuth (Bi) [36][37][38] -based metal halides, which hold potential for X-ray scintillators. Very recently, Rb 2 CuBr 3 33 and Cs 2 NaTbCl 6 39 were shown to be scintillators with high light yield.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, developing a lead‐free and non‐toxic photocatalyst for dye degradation is still of great significance to reduce the risk of secondary pollution and has been proven as a photocatalyst for CO 2 reduction .…”
Section: Photoelectrochemical Applications Of Ihpqdsmentioning
confidence: 99%
“…Quantitative determination of biorecognition elements, heavy metal ion pollution, light intensity and other substances has become an important research topic. Owing to its high sensitivity, selectivity, low background, signal approach and rapid determination, the PEC sensing technique, which can usually use semiconductor QDs to convert the target object into photocurrent signal under light illumination, has attracted extensive attention with attractive application prospect …”
Section: Photoelectrochemical Applications Of Ihpqdsmentioning
confidence: 99%